2021
DOI: 10.1111/1477-9552.12420
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Income Disparity between Farm and Non‐farm Households in the European Union: A Longitudinal Analysis

Abstract: Government interventions in the agricultural sector have been historically justified by the existence of an income disparity between farmers and non-farmers. However, recent studies have found that such disparity is disappearing over time, particularly in the United States. This work offers the first longitudinal systematic assessment on the average income disparity between farm and non-farm units in the European Union, differentiating between old and new Member States. Using the EU-SILC dataset, both broad (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 46 publications
3
17
1
Order By: Relevance
“…For example, unobservable preferences might determine the sorting of households into the farm sector while unobserved characteristics, such as skills, might affect incomes. Marino, Rocchi, and Severini (2021) revisit the EU-SILC dataset using a fixed effects regression methodology to control for these individual unobservable characteristics. Again, the raw data show that farm household incomes are much lower than for nonfarm households, particularly in the newer member states, but there are also significant differences in observable characteristics.…”
Section: Ensuring Food Securitymentioning
confidence: 99%
“…For example, unobservable preferences might determine the sorting of households into the farm sector while unobserved characteristics, such as skills, might affect incomes. Marino, Rocchi, and Severini (2021) revisit the EU-SILC dataset using a fixed effects regression methodology to control for these individual unobservable characteristics. Again, the raw data show that farm household incomes are much lower than for nonfarm households, particularly in the newer member states, but there are also significant differences in observable characteristics.…”
Section: Ensuring Food Securitymentioning
confidence: 99%
“…For instance, in the United States, studies have conclusively shown the disappearance of the farm income problem under any available method of analysis (e.g., El-Osta et al 2007;Katchova 2008;Mishra et al 2002). A similar trend of convergence has been detected also in the EU (e.g., de Frahan et al 2017;Eurostat 2003;Marino et al 2021;OECD 2003;Rocchi et al 2020). de Frahan et al (2017) found that FH incomes are not particularly lower on average than NFH incomes in most OECD countries.…”
Section: The Farm Income Problem and The Role Of The Public Interventionmentioning
confidence: 74%
“…de Frahan et al (2017) found that FH incomes are not particularly lower on average than NFH incomes in most OECD countries. Rocchi et al (2020) and Marino et al (2021) also find that, under certain circumstances, farm units are even richer than their counterparts. However, some have shown a greater income inequality and poverty in the farm community than in the nonfarm community (de Frahan et al 2017).…”
Section: The Farm Income Problem and The Role Of The Public Interventionmentioning
confidence: 94%
“…As for income gap, many scholars have studied the income gap and its changes around the world [43][44][45][46]. These include absolute changes and relative changes.…”
Section: Discussionmentioning
confidence: 99%